Potentiometric multi-syringe flow injection system for determination of exchangeable potassium in soils with in-line extraction - Almeida, M. Inês G. S. (2010)
A multi-syringe flow injection system for the potentiometric determination of exchangeable potassium in soil samples is proposed. Firstly, a manifold was devised to allow determination in soil extracts prepared off-line. It was possible to analyze samples prepared in extractants with different composition (Mehlich or Morgan) without physical or chemical modification of the manifold. A linear dynamic concentration range of 6–391 mg L−1 was obtained, allowing the direct introduction of soil extract without dilution. A determination frequency of 50 h−1 was achieved, with good repeatability for 10 consecutive injections of soil extracts (RSDb3.0%). The in-line preparation of soil extract was implemented by automatic addition of extractant solution to a previously weighed portion of soil, followed by in-line filtration. Good repeatability was attained as the variance of the extraction procedure was not significantly different from the variance obtained in consecutive measurements of the same extract. Furthermore, results comparable to those obtained by off-line extraction and determination by flame emission spectrometry were attained for the two soil samples tested. Using this procedure, a determination frequency of 13 h−1 and a sampling rate of 4 h−1 were achieved.